Early life phenobarbital exposure dysregulates the hippocampal transcriptome - Quinlan, Seán; Khan, Tahiyana; McFall, David; Campos-Rodriguez, Carolina; Forcelli, Patrick A. (Frontiers in Pharmacology, 2024)
Phenobarbital (PB) and levetiracetam (LEV) are the first-line therapies for neonates with diagnosed seizures, however, a growing body of evidence shows that these drugs given during critical developmental windows trigger lasting molecular changes in the brain. While the targets and mechanism of action of these drugs are well understood-what is not known is how these drugs alter the transcriptomic landscape, and therefore molecular profile/gene expression during these critical windows of neurodevelopment. PB is associated with a range of neurotoxic effects in developing animals, from cell death to altered synaptic development to lasting behavioral impairment. LEV does not produce these effects.Here we evaluated the effects of PB and Lev on the hippocampal transcriptome by RNA sequencing.Neonatal rat pups were given a single dose of PB, Lev or vehicle and sacrificed 72 h later-at time at which drug is expected to be cleared. We found PB induces broad changes in the transcriptomic profile (124 differentially expressed transcripts), as compared to relatively small changes in LEVtreated animals (15 transcripts). PB exposure decreased GABAergic and oligodendrocyte markers pvalb and opalin, and increased the marker of activated microglia, cd68 and the astrocyte-associated gene vegfa. These data are consistent with the existing literature showing developmental neurotoxicity associated with PB, but not LEV. The widespread change in gene expression after PB, which affected transcripts reflective of multiple cell types, may provide a link between acute drug administration and lasting drug toxicity